2003
DOI: 10.1002/gepi.10268
|View full text |Cite
|
Sign up to set email alerts
|

Cleft palate, transforming growth factor alpha gene variants, and maternal exposures: Assessing gene‐environment interactions in case‐parent triads

Abstract: We have previously reported a threefold risk of cleft palate only (CPO) among children homozygous for the less common allele A2 at the TaqI marker site of the transforming growth factor alpha gene (TGFA) (Jugessur et al. [2003a] Genet. Epidemiol. 24:230-239). Here we assess possible interaction between the child's TGFA TaqI A2A2 genotype and maternal cigarette smoking, alcohol consumption, use of multivitamins and folic acid. This was done by comparing the strength of genetic associations between strata of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 27 publications
0
35
2
2
Order By: Relevance
“…Even though the test for interaction was not significant in a California case-control study, elevated risk for TGFA TaqI C2-allele carrier in smoking mothers was observed, with OR = 6.1 (95% CI: 1.1-36.1) for CL/P and OR = 9 (95% CI: 1.4-61.9) for CPO . Negative results were also reported in several studies Christensen et al, 1999;Romitti et al, 1999;Beaty et al, 2002;Jugessur et al, 2003). Zeiger et al (2005) performed a meta-analysis and reported an increased risk (OR = 1.95, 95% CI: 1.22-3.10) for CPO in smoker mothers if the infant carried the TaqI C2 allele.…”
Section: Developmental Genes For Oral Clefts Transforming Growth Factmentioning
confidence: 88%
See 1 more Smart Citation
“…Even though the test for interaction was not significant in a California case-control study, elevated risk for TGFA TaqI C2-allele carrier in smoking mothers was observed, with OR = 6.1 (95% CI: 1.1-36.1) for CL/P and OR = 9 (95% CI: 1.4-61.9) for CPO . Negative results were also reported in several studies Christensen et al, 1999;Romitti et al, 1999;Beaty et al, 2002;Jugessur et al, 2003). Zeiger et al (2005) performed a meta-analysis and reported an increased risk (OR = 1.95, 95% CI: 1.22-3.10) for CPO in smoker mothers if the infant carried the TaqI C2 allele.…”
Section: Developmental Genes For Oral Clefts Transforming Growth Factmentioning
confidence: 88%
“…Considerable heterogeneity in the prevalence of the C677T polymorphism throughout the world has been reported (Pepe et al, 1998;Botto and Yang, 2000). Joint effects of MTHFR C677T variant and maternal smoking have been studied in cleft cases from a US population and a Norwegian population (Jugessur et al, 2003), with negative results in both studies.…”
Section: Methylenetetrahydrofolate Reductasementioning
confidence: 99%
“…Recent works in clefts, however, have started to focus on parental contributions too, particularly for the assessment of maternally mediated effects and the effects of imprinting [75,76,77 • ]. Another recent extension of the case-parent triad approach (see Glossary) consists of using information from grandparents to explore the joint effects of maternal and offspring genotypes and to provide a direct estimation of relative risks [78].…”
Section: A Role For Environmental Risk Factorsmentioning
confidence: 99%
“…6,21,[39][40][41][42][43] Our results demonstrated that not only the Tgfβ-pathway genes but also other pathway-related genes might interact each other to regulate medial edge epithelium disintegration and complete palatogenesis (Supplementary Figure 2) In several studies, it has been suggested that there is a gene-environment interaction exists between smoking and TGFα expression for the induction of cleft palate. 8,25,[44][45][46][47][48][49] By using our microarray analysis and filtering cleft palate-related genes, we determined that nicotine is the highly susceptible element of smoking to induce down-regulation of TGFα, which may explain the palatal size abnormality observed in nicotine-treated pups. The presence of partial palatal seam in the newborn pups, which otherwise would have disintegrated at 14.5 to 16.5 dpc indicates: (1) the growth of the palate towards each other to form a seam, although in smaller size and shape, is not altered; (2) the genes that causes immaculate seam disintegration might have been effected by nicotine exposure.…”
Section: Discussionmentioning
confidence: 99%